2019
DOI: 10.21849/cacd.2019.00031
|View full text |Cite
|
Sign up to set email alerts
|

Using actors and peers in the clinical education of stuttering: Results from a mixed methods study

Abstract: Results: Quantitative ratings showed that participants felt more confident explaining information related to the nature of stuttering with the actor compared to the peer. Among some of themes which emerged from the qualitative analysis were that participants viewed their experiences with the actors as natural, genuine, and contributing to new insights in their abilities. Conclusions: The use of actors in the clinical education of stuttering was found to be beneficial to student learning related to their clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…To date, international research investigating simulationbased learning in stuttering has primarily focused on student perceptions (e.g., Hughes et al, 2019;Penman et al, 2021;Vermeulen, 2010). This research has revealed an increase in perceived confidence levels (Hughes et al, 2019;Penman et al, 2021) and an overall positive response to the use of simulation-based learning in stuttering (Hughes et al, 2019;Penman et al, 2021;Vermeulen, 2010). Whilst these results signal perceived beneficial outcomes for students, they neither predict nor equate to student clinical skills in this practice area.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, international research investigating simulationbased learning in stuttering has primarily focused on student perceptions (e.g., Hughes et al, 2019;Penman et al, 2021;Vermeulen, 2010). This research has revealed an increase in perceived confidence levels (Hughes et al, 2019;Penman et al, 2021) and an overall positive response to the use of simulation-based learning in stuttering (Hughes et al, 2019;Penman et al, 2021;Vermeulen, 2010). Whilst these results signal perceived beneficial outcomes for students, they neither predict nor equate to student clinical skills in this practice area.…”
Section: Introductionmentioning
confidence: 99%
“…The SPIRS was also adapted to successfully assess audiology students in a simulation context and termed the Audiology Simulated Patient Interview Rating Scale (ASPIRS) (Hughes et al, 2016). In addition, a student self-evaluation rating scale was recently implemented to guide students' clinical discussions within a stuttering simulation-based learning activity (Hughes et al, 2019). To the authors' knowledge, a tool used by a clinical educator to assess students' clinical skills in stuttering within a simulation-based learning environment does not exist: the SPIRS offered a foundation for developing a tool specific to this context.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst simulation-based research in speech-language pathology has grown significantly in recent years, there has been limited research exploring the use of simu-lation to develop students' clinical skills in stuttering management. Hughes et al (2019) and Vermeulen (2010) explored the benefits of using simulated patients to assist with stuttering competency development. Hughes et al (2019) explored speech-language pathology students' perceptions of their interactions with, first, a peer and then with a simulated patient playing the role of a parent of a child who stuttered.…”
Section: Simulation-based Learningmentioning
confidence: 99%
“…Hughes et al (2019) and Vermeulen (2010) explored the benefits of using simulated patients to assist with stuttering competency development. Hughes et al (2019) explored speech-language pathology students' perceptions of their interactions with, first, a peer and then with a simulated patient playing the role of a parent of a child who stuttered. Results indicated that students experienced a perceived increase in confidence in explaining the nature of stuttering to a simulated patient as opposed to their peer.…”
Section: Simulation-based Learningmentioning
confidence: 99%
See 1 more Smart Citation